2014
DOI: 10.1074/jbc.m114.585166
|View full text |Cite
|
Sign up to set email alerts
|

The Gos28 SNARE Protein Mediates Intra-Golgi Transport of Rhodopsin and Is Required for Photoreceptor Survival

Abstract: Background:The Golgi SNARE, Gos28, plays important roles in vesicular transport during protein trafficking. Results: Mutations in gos28 lead to defective rhodopsin trafficking and retinal degeneration, which is rescued by human Gos28 expressed in transgenic flies. Conclusion: Drosophila Gos28 functions as a t-SNARE in medial-to trans-Golgi transport of rhodopsin during its biosynthesis. Significance: Gos28 represents a novel locus in neurodegeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“…Membrane proteins synthesized on the ER membrane are transported to cis- Golgi cisternae by Rab1 (Satoh et al, 1997), Syx5, and possibly by Sec22 (Zhao et al, 2015). Probably after Gos28 dependent processes (Rosenbaum et al, 2014), basolateral membrane proteins are sorted by AP1 at trans- Golgi/TGN (Satoh et al, 2013) and the two apical membrane proteins are transported together to the recycling endosome (RE) by Rab6 (Iwanami et al, 2016). There is another round of sorting for the two apical pathways at the RE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Membrane proteins synthesized on the ER membrane are transported to cis- Golgi cisternae by Rab1 (Satoh et al, 1997), Syx5, and possibly by Sec22 (Zhao et al, 2015). Probably after Gos28 dependent processes (Rosenbaum et al, 2014), basolateral membrane proteins are sorted by AP1 at trans- Golgi/TGN (Satoh et al, 2013) and the two apical membrane proteins are transported together to the recycling endosome (RE) by Rab6 (Iwanami et al, 2016). There is another round of sorting for the two apical pathways at the RE.…”
Section: Discussionmentioning
confidence: 99%
“…SNAREs seem to mediate membrane fusion in all the trafficking steps of the secretory pathway, except the fusion events in mitochondria and peroxisomes. Recent studies have identified two SNARE proteins, Sec22 and Gos28, which play essential roles in transporting Rh1 to the rhabdomeres (Rosenbaum et al, 2014; Zhao et al, 2015). An extensive Rh1 transport assay revealed that Gos28 is involved in intra-Golgi transport downstream of alpha-mannosidase-II in medial - Golgi (Rosenbaum et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GOS-28 is a Golgi SNARE distributed across the Golgi, including the cis-, medial-, and trans-cisterna and that mediates docking and fusion of vesicles from the ER and within the Golgi apparatus [42]. GOS-28 is a type II transmembrane protein that possesses three N-terminal regulatory helical domains of unknown function, a C-terminal SNARE motif, and a transmembrane domain.…”
Section: Gos-28mentioning
confidence: 99%
“…Maekawa et al reported that GS28 knockout in Caenorhabditis elegans led to a reduction in seam cells and defects in ray formation during development, suggesting that GS28 has roles in cell growth and differentiation. GS28 mutants also show defects in photoreceptor survival in Drosophila …”
Section: Introductionmentioning
confidence: 99%